Study on the Variation of Crude Oil and Flue Gas Components in Flue-Gas-Assisted Steam Flooding. (9th June 2022) - Wei, Yongzhou; He, Xu; Liu, Tingfeng; Liu, Ming; Li, Boliang; Wang, Zhuangzhuang; Li, Binfei
Abstract : In heavy oil development, flue-gas-assisted steam flooding can not only improve oil recovery but also reduce carbon emissions and realize the resource utilization of flue gas. In this paper, the variation in crude oil components produced by steam flooding and flue-gas-assisted steam flooding was studied by indoor displacement experiments and component determination, and the production properties of different components in flue gas, and the influence of flue gas proportion on residual oil components was explored. The results indicate that flue gas can enhance distillation and the production of light components in the steam flooding process. When the ratio of flue gas to steam ranges from 1 : 1 to 3 : 1, the larger the proportion of flue gas injection is, the larger the scope of steam thermal sweep is, the stronger the steam distillation effect is, and the greater the content of light components in residual oil and the change value of each component at the outlet and inlet are. Due to the difference in the dissolution of N2 and CO2 in heavy oil, at the early stage of displacement, the retention rate of CO2 in the formation in the early stage of displacement was higher, and the proportion of CO2 output was lower than the initial injection proportion. With the progress of displacement, the proportion of CO2 gradually increased, and the proportion of N2 gradually decreased. After gas channeling occurs, the N2 proportion increases and gradually approaches the injection proportion. The dissolution and precipitation of flue gas contribute to the formation of foam oil and improve the flow and production of crude oil. The research results are helpful to further understand the mechanism of flue-gas-assisted steam flooding and provide a theoretical basis for the improvement of this technology.